Triglyceride concentrations and non-high-density lipoprotein cholesterol goal attainment in the ODYSSEY phase 3 trials with alirocumab. (1st October 2020) - Vallejo-Vaz, Antonio J; Leiter, Lawrence A; Del Prato, Stefano; Taskinen, Marja-Riitta; Müller-Wieland, Dirk; Bujas-Bobanovic, Maja; Letierce, Alexia; Mandel, Jonas; Samuel, Rita; Ray, Kausik K
Abstract : Aims: Guidelines recommend targeting non-high-density lipoprotein cholesterol to reduce cardiovascular risk. We assessed the impact of baseline triglycerides on non-high-density lipoprotein cholesterol goal attainment in 10 phase 3 trials with alirocumab versus control ( n = 4983). Methods: Trials were grouped into four pools based on alirocumab dose (75–150 mg every 2 weeks), control (placebo/ezetimibe) and statin use. Baseline triglyceride quintiles were built within each pool. Non-high-density lipoprotein cholesterol goal attainment (very high risk: <100 mg/dl; moderate/high risk: <130 mg/dl), low-density lipoprotein cholesterol goal attainment (very high risk: <70 mg/dl; moderate/high risk: <100 mg/dl) and changes from baseline in lipid parameters were assessed at Week 24 among baseline triglyceride quintiles. Results: Higher baseline triglycerides were associated with a worse cardiovascular risk profile. Low-density lipoprotein cholesterol and non-high-density lipoprotein cholesterol increased with higher triglycerides, but the magnitude in non-high-density lipoprotein cholesterol was three- to four-fold higher compared with the increase in low-density lipoprotein cholesterol. Non-high-density lipoprotein cholesterol and low-density lipoprotein cholesterol percentage reductions from baseline with alirocumab were similar regardless of baseline triglycerides. A greater proportion of alirocumab-treated patients attained non-high-density lipoprotein cholesterol and low-density lipoprotein cholesterol goals compared with placebo or ezetimibe. Unlike low-density lipoprotein cholesterol goal attainment, non-high-density lipoprotein cholesterol goal attainment significantly declined with increasing baseline triglycerides ( p < 0.05 for trend tests). A single standard deviation increase in baseline log(triglycerides) was significantly associated with lower odds ratios of attaining non-high-density lipoprotein cholesterol goals in the different pools and treatment (alirocumab/placebo/ezetimibe) groups, unlike low-density lipoprotein cholesterol goal attainment. Conclusion: Individuals with increased triglycerides have higher non-high-density lipoprotein cholesterol levels and lower rates of non-high-density lipoprotein cholesterol goal attainment (unlike low-density lipoprotein cholesterol goal attainment). Alirocumab improves non-high-density lipoprotein cholesterol goal attainment in this population. These results highlight the impact of triglycerides on non-high-density lipoprotein cholesterol and the need for novel therapies targeting triglyceride-related pathways.